Evolution of permeability across the transition from brittle failure to cataclastic flow in porous siltstone. (12th September 2015) - Scuderi, Marco M.; Kitajima, Hiroko; Carpenter, Brett M.; Saffer, Demian M.; Marone, Chris
Abstract Porous sedimentary rocks fail in a variety of modes ranging from localized, brittle deformation to pervasive, cataclastic flow. To improve our understanding of this transition and its affect on fluid flow and permeability, we investigated the mechanical behavior of a siltstone unit within the Marcellus Formation, PA USA, characterized by an initial porosity ranging from 41 to 45%. We explored both hydrostatic loading paths (σ1 = σ2 = σ3) and triaxial loading paths (σ1 > σ2 = σ3) while maintaining constant effective pressure (Pe = Pc – Pp). Samples were deformed with an axial displacement rate of 0.1 μm/s (strain rate of 2 × 10−6 s−1). Changes in pore water volume were monitored (drained conditions) to measure the evolution of porosity. Permeability was measured at several stages of each experiment. Under hydrostatic loading, we find the onset of macroscropic grain crushing (P*) at 39 MPa. Triaxial loading experiments show a transition from brittle behavior with shear localization and compaction to cataclastic‐flow as confining pressure increases. When samples fail by shear localization, permeability decreases abruptly without significant changes in porosity. Conversely, for cataclastic deformation, permeability reduction is associated with significant porosity reduction. Postexperiment observation of brittle samples show localized shear zones characterized by grain comminution. Our data show how zones of shear localization can act as barriers to fluid flow and thus modify the hydrological and mechanical properties of the surrounding rocks. Our results have important implications for deformation behavior and permeability evolution in sedimentary systems, and in particular where the stress field is influenced by injection or pumping.